Exploring the Art of Translation Strategies in Indonesian Culinary Translation - Gudeliva Yunika Lilik Subari (Universitas Sebelas Maret, 2025)
Culinary translation challenges translators in rendering the source text into the target language naturally due to the cultural gap, linguistic differences, and the loss of meaning. The literature review explores the studies of translation strategies in Indonesian culinary translation, focusing on three main themes: strategies, challenges encountered, and suggested solutions by employing a qualitative literature-based research method. The review is to examine the translation strategies employed in translating culinary terms. Translators use various strategies in translating culinary terms. However, translating culinary terms requires the cultural knowledge and language proficiency of both the source language and the target language to get the equivalent meaning in the target text. Translators are encouraged to employ translation strategies that are more flexible and focus on the text’s purpose and audience.